APPLICATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN PROCEDURE TEXT MATERIAL IN CLASS IX OF SMPN SATU ATAP 1 WANASABA - Azhari Arzamnur, Agung (Journal of Educational Studies, 2023)
The purpose of this research is to improve the English learning results on the procedure text material of grade IX students of SMPN 1 Atap Wanasaba. The learning model used in this research is Problem Based Learning (PBL) model. The subjects of this research are grade IX students of SMPN 1 Atap Wanasaba. The number of students is 15 students, 11 male students and 4 female students. This research was conducted in the 2022/2023 school year for a period of 3 months, from January 2023 to March 2023 in the second semester. The methodology of this research is Classroom Action Research (CAR) consisting of two cycles and each cycle consists of two meetings. In each cycle, it consists of planning, implementation, observation and reflection. The data collection technique is to collect the test scores carried out at the end of each learning in each cycle using a test instrument (written test). Data observation was done by looking at the student's activity in the learning process. Data were analyzed using percentage statistical techniques. The results of the study showed that there was an increase in student learning activities in both cycles, from the sufficient category to the good category and the good category increased to very good. The completeness of student learning outcomes increased from 46.66% in the pre-cycle to 73.33% in cycle I and increased to 86.66% in cycle 2. The use of PBL learning model can improve the English learning outcomes on the procedure text recipe material of grade IX students of SMPN 1 Atap Wanasaba in the 2022/2023 school year.